Інтернет-сайт як об'єкт авторського права - Гаряєва, Ганна Михайлівна; Тимців, Микола Михайлович; Білоконь, І. А. (НТУ "ХПІ", 2013)
The article highlights the problems of determinations of rights to own web site. In the article web site is regarded as an object if copyright. Article also describes how to obtain patent for an Internet site.
Keywords: веб-сайти; ім'я доменне; охорона правова; патентування